The Rise of the 'No Party' in England - Toke Aidt; Christopher Rauh (Center for Economic Studies and ifo Institute (CESifo), 2019)
We document a remarkable increase over the past two and a half decades in the fraction of people in England feeling close to no party – the rise of the “no party” – which, today, is close to constituting an absolute majority. We develop a new method to distinguish between age, period, and cohort effects based on individual longitudinal survey data and we show that the rise of the “no party” is driven much more by a secular trend (period effects) than by generation replacement (cohort effects). We show that the increase in “no party” supporters and in their turnout behavior can explain 80% of the observed decline in election turnout in England over the period. A detailed investigation of the dynamics of party identification shows that party political disengagement has become more persistent over time.
Keywords: D72; 330; age-period-cohort effects; party identification; democracy; England; Secular Disengagement Hypothesis